PENGARUH KUALITAS KEHIDUPAN KERJA DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA GURU SMP NEGERI SE-KECAMATAN TELUKNAGA KABUPATEN TANGERANG - Neneng Riyana Novita (Universitas Negeri Jakarta, 2017)
The research was conducted to all teachers of junior higt school districts teluknaga regency of Tangerang. By using a survey method with path analysis applied in testing hypothesis the number 113 teachers as sample was selected by using Slovin formula. Based on the results of data analysis in this research it is concluded: (1) the quality of work life have positive direct effect to job satisfaction; (2) the job involvement have positive direct effect to job satisfaction; (3) the quality of work life have positive direct effect to job involvement. The job satisfaction can be improv through improvement of quality of work life and job involvement.